2018
DOI: 10.18016/ksutarimdoga.vi.452854
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Systematics of Seed Plants in Avşar Campus, Kahramanmaraş Sütçü İmam University (KSU)

Abstract: yerleşkesi tohumlu bitki çeşitliliğini belirlemek ve sistematiğinin oluşturulması amacıyla yapılmıştır. Araştırma alanı Kahramanmaraş ili sınırları içinde ve Davis'in karelaj (Grid) sistemine göre C6 karesinde yer almaktadır. Bu araştırmada, Nisan 2016-Haziran 2017 tarihleri arasında yapılan arazi çalışmalarında toplanan bitki örnekleri değerlendirilmiş ve 65 familya, 194 cinse ait 279 tohumlu bitki taksonu tespit edilmiştir. Bu taksonlardan 2 adeti (% 0.71) (Papaver clavatum, Trigonella kotschyi) Türkiye için… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Accordingly, it is concluded that school principals use their expertise power the most among the power resources sub-dimensions. When the literature is examined [1,18,21,22,25,32,78], it is seen that similar results have been observed. However, there have also been studies in the literature with different results; studies in which the reward power is the highest [9,13,24,79,80], studies in which the legal power is the highest [81], studies in which charismatic power is the highest [10,14,20,82], and the studies with the highest frequency of connection power [18].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Accordingly, it is concluded that school principals use their expertise power the most among the power resources sub-dimensions. When the literature is examined [1,18,21,22,25,32,78], it is seen that similar results have been observed. However, there have also been studies in the literature with different results; studies in which the reward power is the highest [9,13,24,79,80], studies in which the legal power is the highest [81], studies in which charismatic power is the highest [10,14,20,82], and the studies with the highest frequency of connection power [18].…”
Section: Discussionsupporting
confidence: 59%
“…There are many studies in the literature about power supplies. The terms job satisfaction and satisfaction [1,2,[9][10][11][12], organizational commitment [2,13,14], leadership styles and characteristics [15,16], job performance [17][18][19], organizational silence [20,21] organizational cynicism [22], organizational trust [23], organizational climate [24], job stress [17], dedication to work [25] have been found to be related. Studies have focused on the effects of organizational power on the organization and its employees.…”
Section: Introductionmentioning
confidence: 99%
“…The trial area is between 37°35′36 ″ north latitude and 36°49′20 ″ east longitude and approximately 508 m above sea level. The average precipitation and temperature are 719.7 mm and 16.6 °C, and the Mediterranean climate is dominant in experimental area (Uzun et al, 2018). The physical and chemical properties of the lysimeter soil are given in Tables 1 and 2.…”
Section: Study Areamentioning
confidence: 99%
“…The climate induced warming in the Himalaya is experiencing faster rates (0.06 °C/year) than predicted for the other regions of the world 11 13 , raising the likelihood of species extinction in these vulnerable regions. Analyses of temperature trends have shown that temperature increases are greater at the higher altitudes than in the lowlands 14 . Studies suggest that a 0.3 °C rise in global mean temperature per decade will result in potential rise of the global mean surface temperature of about 1–3.5 °C by 2100 15 .…”
Section: Introductionmentioning
confidence: 99%